RESPONSE OF PAPRIKA PLANTS TO THE CONCENTRATION AND FREQUENCY OF LEAF FERTILIZER - Farida, Mukti; Nurjani, Nurjani; Santoso, Eddy (Jurnal Sains Mahasiswa Pertanian, 2020)
This research aims to find out interaction between consentration and frequency of Gandasil leaf fertilizer to Paprika plants. The research was conducted in Experimental Garden of Agriculture Faculty of Tanjungpura University Pontianak with altitude of place 1-2 m on sea surface. This research held on March 03st  up to May 19th 2019. The method of this research is Randomized Completely Design with two treatment factors. The first factor was the concentration (k) of Gandasil leaf fertilizer with 3 levels treatment are k1= 1 g/liter, k2= 2 g/liter, k3= 3 g/liter, and the second factor was the frequency (f) of Gandasil leaf fertilizer with 3 levels treatment are f1= every 5 days, f2= every 10 days, f3= every 15 days, so that obtained 9 treatment combination. Every treatments reapeated as 3 times and consist of 4 sample plants and number of all plants are 108 plants. Observation variable included height of plants, fresh weight of plant, dried weight of plant f. The result of this research showed that the interaction between concentration and frequency of Gandasil leaf fertilizer have been not able to improved production Paprika plants. The interaction between concentration and frequency significantly afffected the heigh of plant  4, and 5 weeks after cultivation, fresh wight of plants,  dried weight of plant. Single factor af concentration significantly affected the height of plant 4 and 5 weeks after cultivation, fresh weight and dried weight of plants. Single factor af frequency significantly affected the heigh of plant 4 and 5 weeks after cultivations, fresh weight and dried weight of plants. The result of the research showed that interaction between concentration 2 g/liter and frequency every 10 days gave the best result to the height of plants  4, and 5 weeks ater cultivation, fresh wight of plants and dried weight of plants.